EVALUASI KELAYAKAN USAHA AYAM POTONG SAMU’ ADUP DI KECAMATAN LUMAR KABUPATEN BENGKAYANG - Sabinus Beni; Ricardus (RISTEK : Jurnal Riset, Inovasi dan Teknologi Kabupaten Batang, 2023)
The Samu' Adup broiler business is a business initiated by students of the Shanti Bhuana Institute of Entrepreneurship study program with various problems experienced, one of which is business planning which is felt to still need to be evaluated because of its existence in the interior of West Kalimantan, namely in Lumar District, Bengkayang Regency. This study uses descriptive qualitative methods to evaluate business feasibility through SWOT analysis. The purpose of this research is to evaluate the feasibility of the Samu' Adup broiler business so that it can run smoothly and get profits and increase business volume. The results of the study show that this business can be continued with various adjustments to the results of the SWOT analysis, including the persistence of business actors who need to be increased, repair of business premises, promotions and sales techniques that are not monotonous at trading places but also marketing using social media, using the COD system and sales with ball pick-up system to the consumer's place.